Conflicts of misfit children in Ini Kisah Adham, Saya & Awan Shiro by Mazny M. R. : a struggle for love, comfort and happiness - Nik Muhamad Affendi, Nik Rafidah; Mohd Hanafiah, Halis Azhan; Awang Pawi, Awang Azman (Gokmen Arslan, 2022)
This research aims to discuss conflicts of misfit children, having struggled in their small community as illustrated in the novel Ini Kisah Adham, Saya & Awan Shiro (‘This is the story of Adham, Awan Shiro and me’). The term ‘conflict’ is widely understood as collision or disagreement within oneself or involving at least two parties over one particular need. Consequently, one is battling with obstacles to achieve the need, hence gradually requires him to make the best decision or to commit the most possible action. The research outlines three objectives to achieve, (1) to identify the characters of misfit children in Ini Kisah Adham, Saya & Awan Shiro by Mazny M. R.; (2) to analyse the conflicts circulated around the misfit children in Ini Kisah Adham, Saya & Awan Shiro by Mazny M. R, and (3) to relate the conflicts of misfit children with the struggle for love, comfort and happiness Ini Kisah Adham, Saya & Awan Shiro by Mazny M. R. This research employs close reading method. The primary source of the research is the novel Ini Kisah Adham, Saya & Awan Shiro by Mazny M. R., first published by The New Straits Times Press (Malaysia) in 2019. The novel is an award winning work, having been the first prize winner of Sayembara Novel Remaja & Kanak-kanak Berita Harian (a novel writing contest for young adults and children organized by Berita Harian). The secondary sources of the research include journals, books, articles, references or other sources that enable further understanding on the issues highlighted in the primary source. To clarify further on ‘conflicts’ that surround the misfit characters, the research employs the theory of conflicts by Neal E. Miller. Miller outlines four types of conflicts that usually one needs to confront in his/her life: (1) approach – avoidance competiton (2) avoidance – avoidance competition (3) approach – approach competition and (4) double approach – avoidance competiton. The results indicate that the two misfit children found in the novel, Hiro and Adham, are psychologically and emotionally distrupted at their school and home after their parents’ death/divorce. Furthermore, the conflicts also happen due to the inability of adults to comprehend conflicts from the children’s perspectives. The bonding of the boys later on convince them to help each other to finally win their struggle for love, comfort and happiness.